2015
DOI: 10.1016/j.cell.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

5′ UTR m6A Promotes Cap-Independent Translation

Abstract: SUMMARY Protein translation typically begins with the recruitment of the 43S ribosomal complex to the 5′ cap of mRNAs by a cap-binding complex. However, some transcripts are translated in a cap-independent manner through poorly understood mechanisms. Here, we show that mRNAs containing N6-methyladenosine (m6A) in their 5′ UTR can be translated in a cap-independent manner. A single 5′ UTR m6A directly binds eukaryotic initiation factor 3 (eIF3), which is sufficient to recruit the 43S complex to initiate transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

36
1,516
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,505 publications
(1,623 citation statements)
references
References 32 publications
36
1,516
1
2
Order By: Relevance
“…Quantification of these modification events suggests they occur in many RNAs (2,3). Importantly, several of these modifications have functional consequences (4)(5)(6). For example, the presence of a single N 6 -methyladenosine within the 5′ UTR of an mRNA increases translation initiation (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of these modification events suggests they occur in many RNAs (2,3). Importantly, several of these modifications have functional consequences (4)(5)(6). For example, the presence of a single N 6 -methyladenosine within the 5′ UTR of an mRNA increases translation initiation (4).…”
mentioning
confidence: 99%
“…Importantly, several of these modifications have functional consequences (4)(5)(6). For example, the presence of a single N 6 -methyladenosine within the 5′ UTR of an mRNA increases translation initiation (4). In addition, the methylation status of cytosine residues within the 3′ UTR of the p16(INK4) human mRNA affects mRNA stability (6).…”
mentioning
confidence: 99%
“…It has been shown that m 6 A modifications have different effects on mRNA translation when the m 6 A modifications occur at different regions of the mRNAs (14 -16). RNA methylation at the 5Ј UTR could promote mRNA translation, whereas RNA methylation at the last exons participated in the 3Ј UTR regulation of mRNAs (15,16 …”
mentioning
confidence: 99%
“…78 It has also become clear that depending on the context of the modification and its localization, for instance in the 5 0 UTR or 3 0 UTR of a transcript, the same protein can coordinate with different cellular machinery and result in very different outcomes. 10,11 While substantial progress has been made in mapping RNA modification sites with high throughput sequencing-based approaches, some major challenges remain. First, in the majority of cases, even if single base resolution can be achieved, we cannot determine the absolute stoichiometry of modification at a given site.…”
Section: Discussionmentioning
confidence: 99%